Hubungan antara Pendekatan Belajar dengan Prestasi Akademik Mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Angkatan 2020 - Irene, Angellita M.; Angmalisang, Elvin C.; Wungouw, Herlina I. S. (e-CliniC, 2024)
Abstract: One of the influencing factors on academic achievement is the learning approach, which is a combination of motivation and strategies that an individual uses to improve his/her knowledge. Learning approach is classified into surface and deep learning approaches. This study aimed to determine the relationship between learning approach and academic achievement of students in the Medical Education Study Program of class of 2020, Faculty of Medicine, Universitas Sam Ratulangi. This was an observational and analytical study with a cross-sectional design. Samples were obtained by using total sampling with inclusion and exclusion criteria. Learning approach data were obtained by using the Revised Study Process Questionnaire 2 Factors (R-SPQ-2F). Data were analyzed using the Fisher Exact test. The results obtained 162 students as samples, dominated by 124 (76.5%) students with deep learning approach, while 38 (23.5%) students used surface learning approach. Furthermore, the majority of students obtained Cumulative Grade Point Average (CGPA) with honors/cum laude (>3.50) amounting to 89 (54.9%) students. The Fisher Exact test, obtained a p-value of 0.936 (p>0.05). In conclusion, there is no relationship between the learning approach and the academic achievement of students in the Medical Education Study Program of class of 2020, Faculty of Medicine, Universitas Sam Ratulangi. Keywords: learning approach; academic achievement; medical students    Abstrak: Salah satu faktor yang memengaruhi prestasi akademik ialah pendekatan belajar (learning approach), yang merupakan gabungan antara motivasi dan strategi yang digunakan seseorang saat mencari pengetahuan. Pendekatan belajar diklasifikasikan menjadi pendekatan belajar permukaan (surface) dan dalam (deep). Penelitian ini bertujuan untuk mengetahui hubungan antara pendekatan belajar dengan prestasi akademik mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Angkatan 2020. Jenis penelitian ini ialah analitik observasional dengan desain potong lintang. Teknik sampling yang digunakan ialah total sampling dengan kriteria inklusi dan eksklusi. Data pendekatan belajar diperoleh menggunakan the Revised Study Process Questionnaire 2 Factors (R-SPQ-2F). Uji statistik dalam penelitian ini ialah uji Fisher Exact. Hasil penelitian mendapatkan total sampel penelitian berjumlah 162 mahasiswa yang didominasi oleh 124 (76,5%) mahasiswa dengan pendekatan belajar dalam (deep), sedangkan 38 (23,5%) mahasiswa menggunakan pendekatan belajar permukaan (surface). Mayoritas mahasiswa memperoleh Indeks Prestasi Kumulatif (IPK) dengan predikat pujian/cum laude (>3,50) berjumlah 89 (54,9%) mahasiswa. Hasil uji Fisher Exact mendapatkan nilai p=0,936 (p>0,05). Simpulan penelitian ini ialah tidak terdapat hubungan antara pendekatan belajar dengan prestasi akademik mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Angkatan 2020. Kata kunci: pendekatan belajar, prestasi akademik, mahasiswa kedokteran